Combining data envelopment analysis and multi-objective model for the efficient facility location-allocation decision - Jae-dong Hong; Ki-Young Jeong (Journal of Industrial Engineering International, 2019)
This paper proposes an innovative procedure of finding efficient facility location-allocation (FLA) schemes, integrating data envelopment analysis (DEA) and a multi-objective programming (MOP) model methodology. FLA decisions provide a basic foundation for designing efficient supply chain network in many practical applications. The procedure proposed in this paper would be applied to the FLA problems where various conflicting performance measures are considered. The procedure requires that conflicting performance measures classified as inputs to be minimized, or outputs to be maximized. Solving an MOP problem generates diverse alternative FLA schemes along with multi-objective values. DEA evaluates these schemes to generate a relative efficiency score for each scheme. Then, using stratification DEA, all of these FLA schemes are stratified into several levels, from the most efficient to the most inefficient levels. A case study is presented to demonstrate the effectiveness and efficiency of the proposed integrating method. We observe that the combined approach in this paper performs well and would provide many insights to academians as well as practitioners and researchers.
Keywords: 650; Facility location-allocation; Data envelopment analysis; Multi-objective programming; Performance measures; Relative efficiency score